Aggregation Patterns of Sensory Sensillae in the Food Canal and Cibarium of Haematobia irritans (Diptera: Muscidae). Issue 1 (17th October 2018) - Joy, James E; Neff, David; Zuzolo, Jenna J; Setser, Emily A; Humbert, Austin A
Abstract: Although mean body lengths of females were significantly greater than males in individuals drawn from two Haematobia irritans (L.) sample populations ( n = 20 females and n = 20 males from West Virginia; n = 20 females and n = 20 males from Georgia), there were no significant differences in food canal lengths for females versus males at either site. Variable numbers (21–37) of setiform sensillae occurred throughout the length of the food canal, but such sensillae were significantly aggregated in the distal-most canal region of both sexes at both sites. There was no significant difference in mean numbers of food canal setiform sensillae between females and males. Four basiconic (campaniform) sensillae were consistently observed in the food canal of every fly; always aggregated in the distal-most canal region. Setiform sensillae in the cibarium also varied in number (6–13), but were significantly aggregated in the median and proximal cibarial regions. Four (occasionally three) peg-like basiconic sensillae were also observed in the cibarium of sample individuals; always in the distal and distal median regions of both sexes. Sensory sensillae (both setiform and basiconic) in both the food canal and cibarium were similarly aggregated for both sexes at both sites. Aggregation of setiform and basiconic sensillae in the food canal suggests that the distal canal region is most critical for sensory input regarding monitoring blood flow, and stress forces brought to bear on the cuticle as the labrum tip penetrates the host's skin.